Evidence of extreme events in wind-induced normal stress of the columns of low- and medium-rise building structures. (12th January 2022) - Suresh, R.; Gopal, R.; Pillai, S. Nadaraja; Chandrasekar, V. K.
Abstract: We designed models for low- and medium-rise building structures with square and rectangular plans and tested the wind-induced normal stress of the building columns. We demonstrate the structures' normal stress response due to the wind load is non-Gaussian and shows evidence of extreme events, which are four to seven times larger than the mean standard deviation. We have estimated the probability distribution function to corroborate the long-tail nature of the extreme events, and randomness of the events is confirmed by plotting inter-event intervals and return maps. Further, the number of extreme events is calculated, which validates the exponentially decaying fit as a function of the number of standard deviations.